Furaltadone, furazolidone and nitrofurazone biotransformation by locally isolated soil fungi / Nur Syahira Mohammad - Mohammad, Nur Syahira (2019)
Microbial transformation is defined as a biological process involving modifying or transforming organic compounds by microorganisms. Nitrofurans (NFs) such as furaltadone (FTD), furazolidone (FZD) and nitrofurazone (NFZ) are widely used in veterinary drugs for poultry and aquaculture. Nitrofurans that fed to animal as an antibiotic and growth promoter creates significant toxicity and carcinogenic effects on human health. Other than that, the excretion of chicken faeces which contain these nitrofurans residues into soil cause soil contamination which were then may also enter into water system. Soil fungi as a mycoremidiation can be used as an approach to treat soil contamination.